Distribution, Status, and Life History Aspects of Two Rare Logperches, Percina burtoni and Percina apina - Jeffrey W Simmons (Southeastern Fishes Council Proceedings, 2021)
The Blotchside Logperch, Percina burtoni, and Tennessee Logperch, Percina apina, are Tennessee-Cumberland River drainage endemics that have experienced range reductions due to anthropogenic influences. All known collection records were gathered to fully describe the historical distribution of these species for comparison to their currently inhabited range. Discussion of major impacts to rivers that contain or contained these species is included for an understanding of factors that may have influenced contemporary distributions. Extensive field surveys were conducted during 2014 to 2017 to aid in determination of the current status and distribution of populations. New information of previously unreported or undetected populations, population status, life history observations, and longevity estimates are presented.
Keywords: Tennessee-Cumberland Rivers; Percidae; natural history records; habitat use